Silat Tempur League: The Analysis of Athletes Performance in 2019 Competitions - Aziz, Nur Azizah Abdul; Shapie, Muhamad Nizam Mohamad; Indrayuda, Indrayuda; Al-Syurgawi, Dahlia; Rahim, Mohamad Rahizam Abdul; Abdullah, Nagoor Meeara; Parnabas, Vincent; Nawai, Nasru Syazwan; Samsudin, Hazim; Kassim, Rezian-na Muhammed; Nor, Mohad Anizu Mohd (International Martial Arts and Culture Journal, 2023)
Background and aim. There are two types of sparring in silat: Silat olahraga and Silat tempur. Silat tempur is a combative sport focused on children, particularly beginners aged 7 to 13. The competition was introduced to prepare young athletes for sparring in Silat olahraga and to improve combative techniques among young silat exponents. The arena, which resembles a fencing platform, facilitates the execution of silat techniques during competition. This study aims to describe the development and implementation of Silat tempur as a preparatory competition for young athletes.Methods.  This study employed a secondary data analysis approach using data obtained from the Pertubuhan Seni Gayung Fatani Malaysia website and official competition records. The data focused on the 2019 Silat tempur league, which consisted of four competition series.Results The findings show that the Silat tempur competition has developed into a structured league involving approximately 200 silat exponents from ten active silat clubs in Malaysia. It represents the first silat league established globally and demonstrates a systematic approach to developing young athletes’ combat skills.Conclusions.        Silat tempur serves as an effective platform for enhancing fundamental combat skills and preparing young exponents for higher-level competitions in Silat olahraga. Its structured format contributes to athlete development and promotes the preservation and global recognition of Malay martial arts